Environmental disaster, victims, and conflict : the environment-security nexus in the context of Southeast Asia - Hew, Guo You (2018)
Environmental degradation is affecting everyone on this planet, and Southeast Asia is no exception. The rapid industrialisation of countries has seen the unprecedented production and release of greenhouse gases into the atmosphere and contributes to global warming and climate change. Global warming has in tum led to other environmental degradation such as erratic weather events, which in tum affected millions of people around the world. Exploitation of resources by foreign multinational companies (MNCs) has also resulted in environmental degradation. These factors have led to weakened states that are unable to distribute scarce resources fairly to all groups and hence exacerbate existing domestic and international tensions and therefore resulting in armed confrontations, or even full-scale wars. This thesis studies three cases in the context of Southeast Asia, and provides policy recommendations to effectively manage the environment-security nexus in the region.